Good for now but not forever: Officials' perspectives on the relevance of the effectiveness agenda and the need for change - Rachael Calleja; Beata Cichocka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper investigates whether the current effectiveness agenda-agreed during the 2011 Busan High Level Forum on Development Effectiveness-continues to define best practice in development amidst a rapidly changing development landscape. To do so, we surveyed officials from development agencies and partner countries to understand whether the effectiveness agenda remains relevant for officials who manage official development assistance (ODA) flows, and if not, how it should change. We find that while respondents believe that the effectiveness agenda is relevant, there is strong demand to revise or renew the agenda to overcome technical, strategic, and political challenges that are limiting its implementation. Based on our survey findings, we propose a simple framework for considering options for change, centered around trade-offs related to the inclusiveness of the agenda and the political will available for reform. We conclude by proposing four possible reform scenarios for the next phase of the effectiveness agenda.
Keywords: 330; effectiveness; development cooperation; development agencies; survey; politics